In Vitro Culture of Pittosporum pentandrum (Bl.) Merr. - Vargas-Zamora, Cecilia (Science Diliman: A Journal of Pure and Applied Sciences; Vol 4 No 2 (1992), 2007)
In vitro culture of Pittosporum pentandrum was done in glass containers with nutrient medium, under aseptic conditions. Several explants were tried. The most successful was the very young leaf blade with midrib, cut 6 x 5 millimeters, grown in an agar culture medium of 1 liter Revised Murashige and Skoog Medium supplemented with the cytokinin benzyl adenine (10 and 15 milligrams) and a combination of two auxins, namely, naphthalene acetic acid (0.25 milligram) and dichlorophenoxyl acetic acid (0.25 milligram), producing an initial stage of development (callus) up to organogenesis (plantlet formation).